Pengembangan Aneka Produk Hilir dari Biji Kakao untuk Meningkatkan Pengetahuan dan Pendapatan Masyarakat - Mahrizal, Mahrizal; Julia, Julia; Arjuniadi, Arjuniadi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The lack of understanding of cocoa farmers regarding cocoa bean processing technology and the absence of process standards for producing quality dry cocoa beans and producing downstream products are problems that need attention. Efforts to overcome the problems faced by residents of Kreb Paloh Village and Capa Paloh Village, Suyo Paloh Village and Siron Village, Paloh Village, Padang Tiji District, Pidie Regency, through PKM activities it is hoped that the community will be able to process cocoa beans which have been directly sold to collectors after harvest. become a product that has high economic value so that it can increase people's income. Methods for carrying out activities include outreach, field observations, training in processing raw material selection, fermentation of cocoa beans in wooden boxes measuring 32 cm long, 32 cm wide and 42 cm high, with a capacity of 40 kg. Wet cocoa beans in each box. Drying and processing of cocoa beans is carried out under direct sunlight to reduce the water content below 7.5%. The production of quality cocoa powder is obtained by roasting and grinding it using a flouring machine. Cocoa powder is used to produce various products ranging from chocolate bars, chocolate cake, chocolate drinks, chocolate candy and chocolate jam. Monitoring and evaluation is used to monitor and evaluate the continued implementation of hygienic and quality cocoa bean fermentation by fostered partners on an ongoing basis after the operation is complete. 95% of target partners have the capacity to produce hygienic and high quality cocoa beans. 90% of target partners can trade various products produced from cocoa beans.